2020
DOI: 10.1371/journal.pone.0239457
|View full text |Cite
|
Sign up to set email alerts
|

PCR-based detection and serovar identification of Salmonella in retail meat collected from wet markets in Metro Manila, Philippines

Abstract: This study aimed to detect Salmonella from retail meat collected from nine wet markets in Metro Manila, and identify the subtypes of Salmonella isolates using molecular serotyping assays from previously developed primers. Of the 720 collected meat samples, 57.64% were found to be Salmonella-contaminated. The most predominant serogroup was Salmo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
0
24
0
2
Order By: Relevance
“…However, the serotype or ST was not contemplated for sample referral and thus our results should be representative of the population. Twelve of the NTS serotypes identified in this study, including the dominant S. Enteritidis and monophasic S. I 4, [5],12:i:-, were previously reported from retail meat in the Philippines, 27 suggesting a potential foodchain reservoir. The monophasic variant of S. Typhimurium (serovar I 4, [5],12:i:-) ST34 rose in prevalence in Europe since the early 2000s and disseminated across the world likely via the food-chain, especially pigs and pig meat, 28 which is the most consumed livestock meat in the Philippines.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, the serotype or ST was not contemplated for sample referral and thus our results should be representative of the population. Twelve of the NTS serotypes identified in this study, including the dominant S. Enteritidis and monophasic S. I 4, [5],12:i:-, were previously reported from retail meat in the Philippines, 27 suggesting a potential foodchain reservoir. The monophasic variant of S. Typhimurium (serovar I 4, [5],12:i:-) ST34 rose in prevalence in Europe since the early 2000s and disseminated across the world likely via the food-chain, especially pigs and pig meat, 28 which is the most consumed livestock meat in the Philippines.…”
Section: Discussionmentioning
confidence: 55%
“…Enteritidis and monophasic S . I 4, [5],12:i:-, were previously reported from retail meat in the Philippines, 27 suggesting a potential food-chain reservoir. The monophasic variant of S .…”
Section: Discussionmentioning
confidence: 99%
“…The method for isolation of Salmonella was followed as per the protocol described by Santos et al (2020) . About 25 g of the sample was aseptically homogenized and inoculated into 225 ml of buffered peptone water (M614, HiMedia, India) in a sterile jar.…”
Section: Methodsmentioning
confidence: 99%
“…occurrence in wet markets are poor animal keeping conditions (overcrowding, cramped cages, transport mortality, wrong or insufficient food, proximity to other animal and species, stress, injuries and diseases), poor sanitation (lack of toilets and hand washing stations) and the possibility to contaminate fresh food and meat by shedding bacteria from wildlife animals [137,138]. To date, a lot of studies relied on the contamination of different types of meat including chicken, beef and pork by Salmonella enterica in China, Philippines, Malaysia and Vietnam [139][140][141]. The studies from Asia also confirmed presence of virulence genes and multi drug resistant and ESBL producing (extended-spectrum beta-lactamases) fenotypes of S. enterica isolated from meat sampled in wet markets [142,143]…”
Section: The Importance Of Wildlife Tradementioning
confidence: 99%